Hamlet apostrophising the skull, from the original picture by Sir Thomas Lawrence in the National Gallery - Rogers, John (Tufts Archival Research Center, 2008)
This illustration is from Charles Knight's "London," Vol. 6. This image was inserted by Edwin C. Bolles and is not found in the original.